Long-term Seizure Outcome and Prognostic Factors After Extratemporal Epilepsy Surgery - นิวัฒน์ภูมินทร์ ผดุงชาญ; สกุลณะมรรคา สิรรุจน์; ชินวลัญช์ โยธิน; ณ บางช้าง ชาครินทร์ (Thai Journal of Neurological Surgery, 2025)
Background: Surgery is an important therapeutic option in patients with intractable epilepsy. Seizure outcome after resective surgery for patients in extratemporal epilepsy vary tremendously in the literature with short duration time of follow-up. Objective: To assess seizure outcome and prognostic factors in patients who had undergone extratemporal epilepsy surgery for management of intractable seizures. Methods: Independent, experienced surgeon retrospectively reviewed a single surgeon database between 2003 and 2013 and identified 50 patients who underwent extratemporal epilepsy surgery for intractable seizure. We evaluated the correlation between the seizure outcome and the following clinical parameters (demographic data, preoperative factors including MRI brain and seizure information, location of resection, neuropathology reports and extent of resection). Multivariable analysis was performed to assess prognostic factors for seizure outcome. Results: FForty-five patients were performed resective epilepsy surgery (frontal resection 42%, parietal resection 20%, occipital resection 6% and multilobar resection 22%). One patient underwent hemispherectomy (2%) and four patients did not undergo resection (8%) due to epileptogenic foci on cortical eloquent area. Forty-seven patients (94%) underwent two-staged operation for subdural grid implantation. Median follow-up was 4.67 years (range 0.67-9.33). Seizure remission was 36% and seizure cure was 20%. The postoperative Engel Class I outcome was 64% at 1 year, 48% at 2 years, 38% at 3 years and 32% at 5 years. On multivariable analysis, presence of generalized tonic-clonic seizure, (p=0.039) and incomplete resection of epileptogenic foci (p=0.01) were independent poor prognostic factors. Conclusion: Extratemporal epilepsy surgery is effective in selected patients according to findings on long-term follow-up.